Efektifitas Penggunaan Media Video Animasi terhadap Pengetahuan Pencegahan Pelcehan Seksual pada Anak Usia Dini di TK Aisyiyah Kota Bukittinggi - Kartika Mariyona; Pagdya Haninda Nusantri Rusdi (Universitas Batanghari Jambi, 2022)
There are more and more cases of sexual harassment crimes in Indonesia, not only among teenagers but also young children who are the targets of sexual crimes. What happened made the government issue a law as a preventive measure to reduce the level of sexual violence against children, namely Law No. 35 of 2014 concerning Child Protection with the aim of